Strengthening the health workforce to support integration of HIV and noncommunicable disease services in sub-Saharan Africa. (1st July 2018) - Rabkin, Miriam; de Pinho, Helen; Michaels-Strasser, Susan; Naitore, Doris; Rawat, Angeli; Topp, Stephanie M.
Abstract : Objective: The successful expansion of HIV services in sub-Saharan Africa has been a signature achievement of global public health. This article explores health workforce-related lessons from HIV scale-up, their implications for integrating noncommunicable disease (NCD) services into HIV programs, ways to ensure that healthcare workers have the knowledge, skills, resources, and enabling environment they need to provide comprehensive integrated HIV/NCD services, and discussion of a priority research agenda. Design and methods: We conducted a scoping review of the published and 'gray' literature and drew upon our cumulative experience designing, implementing and evaluating HIV and NCD programs in low-resource settings. Results and conclusion: Lessons learned from HIV programs include the role of task shifting and the optimal use of multidisciplinary teams. A responsible and adaptable policy environment is also imperative; norms and regulations must keep pace with the growing evidence base for task sharing, and early engagement of regulatory authorities will be needed for successful HIV/NCD integration. Ex-ante consideration of work culture will also be vital, given its impact on the quality of service delivery. Finally, capacity building of a robust interdisciplinary workforce is essential to foster integrated patient-centered care. To succeed, close collaboration between the health and higher education sectors is needed and comprehensive competency-based capacity building plans for various health worker cadres along the education and training continuum are required. We also outline research priorities for HIV/NCD integration in three key domains: governance and policy; education, training, and management; and service delivery.